Factors effecting Corporate Cash Holdings: A Case of Fuel and Power Sector in Pakistan - Laraib Zafar (UW Journal of Management Sciences, 2021)
Purpose: The topic on cash holding has enticed strong debate in the field of finance. A number of researchers have studied the cash holding patterns and its determinants in developed economies while a little attention is given to the corporate cash holdings (CCH) in developing economies. Pakistan is developing country so the objective of this research study is to determine the impact of micro-economic and macro-economic determinants of CCH in the Fuel and Power sector in Pakistan. Design/Methodology: To achieve the desired objective cash and cash equivalent is taken as dependent variable, whereas micro level variables leverage (LEV), dividend payout (DIV), growth opportunity (GO), firm size (FS) and macro variables inflation (CPI), gross domestic product (GDP), short term interest rate (IR) are used as independent variables. The study used annual data for fuel and power sector and is obtained from annual reports of firms and State Bank of Pakistan (SBP) for the period 2013- 2018. Feasible Generalized Leased Square (FGLS) technique has been used to investigate the said relationship. Findings: The study reports some significant and insignificant impacts of micro and macro-economic factors on the corporate cash holdings. Implications: The study contributes to the literature as well as the findings of this research are beneficial for policy and decision makers to make clear understanding and knowledge on corporate cash holding pattern.